(untitled) (SAARC Journal of Agriculture, 2021)
The tropical vegetable, brinjal is cultivated throughout the year in Bangladesh but the crop is infested by a number of insects including jassid. This study investigated the effects of different biophysical and biochemical characteristics of twelve brinjal germplasms on the abundance and infestation of jassid. The experiment was conducted during September 2018 to March 2019 in Gazipur, Bangladesh with twelve brinjal germplasms namely BD-7320, BD-7328, BD-9952, BD-10154, BD-10158, BARI Begun-1, BARI Begun-4, BARI Begun-5, BARI Begun- 6, BARI Begun-7, BARI Begun-8 and BARI Begun-9. The incidence of jassid was recorded from 3rd December to 26th March, and the lowest population was found on BARI Begun- 6. Among the biophysical traits, plant height, number of branch and leaf per plant, and leaf area exerted significant positive correlation; whereas trichome on lower and upper surfaces of leaf, spine per stem and leaf showed significant negative correlation with the abundance of jassid. On the other hand, moisture, reducing sugar, total sugar and protein content of the leaves and fruits, chlorophyll content of the leaves exerts significant positive correlation but ash and pH contents of the leaves and fruits were negatively correlated with the abundance of jassid. Jassids showed the lowest level of leaf infestation on BARI Begun-6, which could be for further analysis to develop jassid resistant brinjal. SAARC J. Agric., 19(1): 81-91 (2021)